Finska vinterkriget - Björk, Simon (Linnéuniversitetet, Institutionen för kulturvetenskaper (KV), 2020)
In this paper, you will be accompanied by a press-historical survey over a three-day period, with three newpapers as the main source. Aftonbladet, Norrskensflamman and Svenska Dagbladet, in my investigation the newspapers have completely different political views. The survey is based on how the magazines choose to present the three themes I have chosen to investigate. My themes are the course of war, Finnish politics and foreign opinion. Norrskensflamman never writes anything about the course of war, it may be because they do not want to present that the Red Army does not really manage to achieve anything at all. Norrskensflamman uses valuable words such as fascists, hypocrites, liars and so on to discuss Finnish politics. The image of the Soviet Union Norrskensflamman presents is that their purpose is to rescue the Finnish people from the oppressive goverment and the people government is considered the Finnish people who revolted and with help of the Red Army expel the fascists out of Finland. Foreign opinion largely tells the newspaper that the United States and Britain will not participate in the war for various reasons. Norrskensflamman mention Germany as despite to their alliance with the Soviet Union, they really sympathize with Finland and that Germans are worried about the Soviet Union’s increasing influence in Europe and in the Baltic Sea. Svenska Dagbladet and Aftonbladet write their war reports fairly similary. However there are still significant differences and that is: Aftonbladet writes more exalted about the Finnish war efforts than Svenska Dagbladet and has a writer who calls himself G.M. who writes that the Finnish army is fighting extremly well ands shoots very well, causing great losses to the enemy. Svenska Dagbladet and Aftonbladet portray Finnish politics in fairly similar ways, but there are still some differences. Aftonbladet presentes two government shifts, while Svenska Dagbladet and Norrskensflamman only presents one. In addition, Aftonbladet writes in more valuble words about why they ...